$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}{\| #1 \|}$$ $$\newcommand{\inner}{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# Derivatives The Easy Way

$$\newcommand{\vecs}{\overset { \rightharpoonup} {\mathbf{#1}} }$$ $$\newcommand{\vecd}{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}{\| #1 \|}$$ $$\newcommand{\inner}{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}{\| #1 \|}$$ $$\newcommand{\inner}{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

## Constant Rule and Power Rule

We have seen the following derivatives:

1. If f(x) = c, then f '(x) = 0
2. If f(x) = x, then f '(x) = 1
3. If f(x) = x2, then f '(x) = 2x
4. If f(x) = x3, then f '(x) = 3x2
5. Iff(x) = x4, thenf '(x) = 4x3

This leads us the guess the following theorem.

 Theorem d xn = nxn-1 dx

Proof:

We have ## Applications

Example

Find the derivatives of the following functions:

1. f(x) = 4x3 - 2x100

2. f(x) = 3x5 + 4x8 - x + 2

3. f(x) = (x3 - 2)2

Solution

We use our new derivative rules to find

1. 12x2 - 200x99

2. 15x3+32x7-1

3. First we FOIL to get

[x6 - 4x3 + 4] '

Now use the derivative rule for powers

6x5 - 12x2

Example:

Find the equation to the tangent line to

y = 3x3 - x + 4

at the point(1,6)

Solution:

y' = 9x2 - 1

at x = 1 this is 8. Using the point-slope equation for the line gives

y - 6 = 8(x - 1)

or

y = 8x - 2

Example:

Find the points where the tangent line to

y = x3 - 3x2 - 24x + 3

is horizontal.

Solution:

We find

y' = 3x2 - 6x - 24

The tangent line will be horizontal when its slope is zero, that is, the derivative is zero. Setting the derivative equal to zero gives:

3x2 - 6x - 24 = 0

or

x2 - 2x - 8 = 0

or

(x - 4)(x + 2) = 0

so that

x = 4 or x = -2

Derivative of f(x) = sin(x)

Proof: d/dx cos(x)

Larry Green (Lake Tahoe Community College)